THE EFFECT OF ORGANIC FERTILIZER WITH MATERIALS MIXED BY THE SIDE OF PALM OIL MILL AND BALI CATTLE MANURE AGAINST GROWTH SWEET CORN (Zea mays) - Ida Ketut Mudhita; Saprudin Saprudin (Bantara Journal of Animal Science, 2019)
This research aim are to examine the effect of the treatment of organic fertilizer from waste palm oil mill and cow manure on the growth of Zea mays and determine the optimum dose of organic fertilizer. This research was conducted in Kapitan Village, Kumai District, West Kotawarigin Regency, Central Kalimantan. There were 4 treatments of the research: organic fertilizer with a dose of 0 tons/ha (P0), 5 tons/ha (P5), 10 tons/ha (P10) and 15 tons/ha (P15) with 3 replications. All treatments were given NPK Mutiara fertilizer at a dose of 200 kg/ha as a basic fertilizer. Zea mays planted in 4 plots 4 treatments with 3 plots of repetition, a total of 12 plots. The spacing was 50x40 cm, the number of corn plants is 56/plot, a total of 672 plants for 12 plots. NPK fertilizer was given 240 g plot. Organic fertilizer P0: 0 kg/plot, P5: 6 kg/plot total 3 plots 18 kg, P10: 12 kg total 36 kg, P15: 18 kg total 54 kg. Parameters observed were plant height, leaf area, fresh weight, dry weight and plant growth rate at 21, 28, 35, 42 and 49 days after planting. The design of the research used a Completely Randomized Design (CRD) in a directional pattern, performed a duncant test if there were differences. The results showed that at the age of 49 days: plant height increased 18% (P5), 20% (P10) and 38% (P15); leaf area increased 42% (P5), 71% (P10), 106% (P15); fresh weight increased by 16% (P0), 86% (P10), 96%: plant growth rate increased by 40% (P5), 248% (P10), 272% (P15) compared to P0. The conclusion is that the higher the dose of organic fertilizer given results in higher plant growth as well, with the optimal dose of organic fertilizer giving a dose of 10 tons/ha.